Learning Effectiveness of Using E-Assignment Application as a Learning Model with Jigsaw Method - Erdisna; Sri Restu Ningsih; Deval Gusrion; Rahmat Hidayat; Weni Kurnia Sari (Jurnal Teknologi Informasi dan Pendidikan, 2026)
Effective learning for students is when a conducive learning atmosphere is created and the achievement of educational goals in higher education is achieved. Furthermore, technological advances in learning and learning strategies are very important in the higher education learning process, considering all student conditions, both internal and external. This study aims to develop an e-assignment application as an effective learning medium during the pandemic and measure the effectiveness of the e-assignment application using the Jigsaw method. The research was conducted on students in the Database Design course. The system used in this exploration is the ADDIE( Analysis, Design, Development, perpetration, Evaluation) model, one of the models that attendants in developing effective, dynamic literacy and supports learning itself. This research resulted in the development of an e-assignment application that was effectively used in the learning process for students and lecturers at universities.